Exploring impacts of vegetated buffer strips on nitrogen cycling using a spatially explicit hydro-biogeochemical modeling approach. (April 2017) - Klatt, S.; Kraus, D.; Kraft, P.; Breuer, L.; Wlotzka, M.; Heuveline, V.; Haas, E.; Kiese, R.; Butterbach-Bahl, K.
Abstract: Agriculture has been recognized as a major anthropogenic source of surplus loads of nitrogen in the environment. Losses of nitrate via subsurface pathways are severely threatening groundwater and surface waters. This study explored the capability of a coupled hydro-biogeochemical spatially explicit model, simulating nitrogen cycling in agricultural soils and the associated fate of excess nitrate subjected to vertical and lateral displacement towards water bodies. Different vegetated buffer strips (VBS) were tested for their nitrate retention capability and impacts on N 2 O and N 2 emissions. The effectiveness of a VBS to remove nitrate by denitrification strongly depends on soil characteristics and hydrological flow paths. Simulated N 2 emissions from VBS with high soil moisture were up to twenty-fold compared to VBS where groundwater levels were low. Simulated streamwater nitrate concentrations without VBS were 3.7 mg NO 3 − l −1 and showed a decrease to 0.1 mg NO 3 − l −1 for a 20 m VBS. Highlights: The coupled hydro-biogeochemical model simulates 3D water and nutrient displacement. The hydro-biogeochemical model enables studying vegetated buffer strip functioning. Mitigation of nitrogen losses strongly depends on site-specific conditions. Fruitful collaboration of a fair number of interdisciplinary science communities.